Research on the improvement of rural resorts in Ukraine - Bialkovska, Oksana; Chaikovskyi, Oleh (Turystyka i Rozwój Regionalny, 2022)
The development of resort services is an integral part of the complex socio-economic development of the rural territories in Ukraine. The country has huge potential for developing different kinds of resorts. To attract consumers of tourist services to rural holiday homes and estates and to improve the quality of rural green tourism (rural hospitality) services in the post-COVID period, taking into account sanitary and hygienic requirements is desirable, by using the recommendations of the “Safe travel” protocol and from EU project “Supporting the development of the system of geographical indications in Ukraine” results. The creation of a legislative framework and strengthening administrative capacity, marketing activities for the rebranding of “sensitive” products, registration of Ukrainian products under Geographical Indication (GI) sign and promotion of their availability on the market, planning projects for the development of rural areas to attract tourism to the regions can benefit in the development of tourist infrastructure in rural areas.